Smart Contracts and the Coase Conjecture - Brzustowski, Thomas; Georgiadis-Harris, Alkis; Szentes, Balázs (American Economic Review, 2023)
This paper reconsiders the problem of a durable-good monopolist who cannot make intertemporal commitments. The buyer’s valuation is binary and his private information. The seller has access to dynamic contracts and, in each period, decides whether to deploy the previous period’s contract or to replace it with a new one. The main result of the paper is that the Coase conjecture fails: the monopo-list’s payoff is bounded away from the low valuation irrespective of the discount factor. (JEL D42, D82, D86, L12)